The genetic variant rs55986091 HLA-DQB1 is associated with a protective effect against cervical cancer - Vinokurov, Michael A.; Mironov, Konstantin O.; Domonova, Elvira A.; Romanyuk, Tatiana N.; Popova, Anna A.; Akimkin, Vasiliy G. (Frontiers in Oncology, 2023)
Introduction Cervical cancer (CC) is a prevalent malignancy affecting women globally. The primary causative factor of CC is the high-risk oncogenic human papillomavirus (HR-HPV). However, it is noteworthy that not all women infected with HR-HPV develop cancer, indicating the potential involvement of genetic predisposition in the development of CC. This study aims to identify genetic risks and their distribution in groups of women with different epidemiological features of HR-HPV. Materials and methods A comparison was conducted among four groups of women, comprising 218 HPV-negative women, 120 HPV-positive women, 191 women diagnosed with cervical intraepithelial neoplasia (CIN) grade 2 or 3, and 124 women diagnosed with CC. The analysis focused on four single nucleotide polymorphisms (SNPs): rs55986091 in HLA-DQB1, rs138446575 in TTC34, rs1048943 in CYP1A1, and rs2910164 in miRNA-146a. Results The rs55986091-A allele exhibited a protective effect within the “CC” group when compared to the “HPV-Negative” group (OR = 0.4, 95% CI= 0.25-0.65) using a log-additive model. Additionally, similar protective effects were observed in the “CIN 2/3” group compared to the “HPV-Negative” group (OR = 0.47, 95% CI = 0.28-0.79). Conclusion The data obtained emphasize the importance of developing PCR-based diagnostic kits for the identification of SNP alleles, particularly for rs55986091, among HR-HPV-positive women within the Russian population.